2016
DOI: 10.1515/mammalia-2015-0175
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of jaguars and pumas and their relationship to those of their potential prey in the Brazilian Pantanal

Abstract: Jaguar and puma are the largest cats in the American continent. Competition between both species is expected due to similarities in diet and habitat use. The objective of this study was to test whether temporal separation exists between these two species and to analyze whether their activity patterns coincide with those of some of their potential prey. We used data from camera trapping to estimate activity patterns and measure the overlap between activity distributions using kernel density. The activity of jag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
4
14
0
1
Order By: Relevance
“…We assessed the daily activity of pumas and their prey within a well-preserved Andean Forest in which other large predators such as jaguars (Panthera onca, Linnaeus 1758) are absent. Pumas showed a nocturnal and crepuscular activity that is geographically consistent with studies made in other Neotropical areas (Scognamillo et al, 2003;Monroy-Vilchis et al, 2009;Harmsen et al, 2009;Blake et al, 2012;Foster et al, 2013;Zanón Martínez et al, 2016;Cáceres-Martínez et al, 2016;Porfirio et al, 2017;Azevedo et al, 2018;Guerisoli et al, 2019;Osorio et al, 2020). Therefore, factors other than habitat features (such as human disturbance and prey availability) may more likely drivers of the puma's activity patterns (Harmsen et al, 2011;Suraci et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…We assessed the daily activity of pumas and their prey within a well-preserved Andean Forest in which other large predators such as jaguars (Panthera onca, Linnaeus 1758) are absent. Pumas showed a nocturnal and crepuscular activity that is geographically consistent with studies made in other Neotropical areas (Scognamillo et al, 2003;Monroy-Vilchis et al, 2009;Harmsen et al, 2009;Blake et al, 2012;Foster et al, 2013;Zanón Martínez et al, 2016;Cáceres-Martínez et al, 2016;Porfirio et al, 2017;Azevedo et al, 2018;Guerisoli et al, 2019;Osorio et al, 2020). Therefore, factors other than habitat features (such as human disturbance and prey availability) may more likely drivers of the puma's activity patterns (Harmsen et al, 2011;Suraci et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…As opportunistic predators, jaguars and pumas feed on a large variety of prey, but they mainly consume medium to large-sized prey (Emmons, 1987;Taber et al, 1997;Núñez et al, 2000;Monroy-Vilchis et al, 2009). Some studies have suggested that the activity patterns of these large felids may be determined by those of their main prey (Harmsen et al, 2011;Foster et al, 2013;Porfirio et al, 2017). The Southern Coati followed the diurnal pattern observed in another area of the Pantanal (Bianchi et al, 2016).…”
Section: Resultsmentioning
confidence: 90%
“…Jaguar and puma are able to adjust their activity to reduce their foraging energy expenditure, by matching their activity to that of their main prey species [ 30 , 67 ]. We cannot rule out the option that prey abundance and some other habitat characteristics affects temporal activity [ 29 ], and consequently temporal partitioning between apex predators.…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to the difficulty in obtaining data across broad spatial scales required to study these ecological processes, as well as sufficient records of species that frequently occur at low densities and/or exhibit elusive behavior. Most studies discuss species interactions at local scales (e.g.,[ 11 , 15 , 30 ]), but how predators change their behavior as they move through heterogeneous landscapes remains largely unexplored. Conducting multi-site comparisons of spatial distributions and activity budgets of co-existing wild cats will be important to improve understanding of mechanisms of coexistence.…”
Section: Introductionmentioning
confidence: 99%